2012
DOI: 10.1530/eje-11-1061
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of pioglitazone and metformin on circulating sclerostin and biochemical markers of bone turnover in men with type 2 diabetes mellitus

Abstract: Objective: Patients with type 2 diabetes mellitus (T2DM) have an increased risk of fractures and thiazolidinediones (TZDs) increase this risk. TZDs stimulate the expression of sclerostin, a negative regulator of bone formation, in vitro. Abnormal sclerostin production may, therefore, be involved in the pathogenesis of increased bone fragility in patients with T2DM treated with TZDs. Methods: We measured serum sclerostin, procollagen type 1 amino-terminal propeptide (P1NP), and carboxy-terminal cross-linking te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 42 publications
4
40
0
4
Order By: Relevance
“…In patients with T2DM, the increase of serum sclerostin is associated with a significant decrease in the b-catenin serum concentration, suggesting, indeed, that sclerostin signaling is modulated in diabetes (31). On one hand, this gives support to the hypothesis that bone, which produces almost all the available sclerostin, may play a role also in glucose metabolism and insulin resistance (8,32,35). On the other hand, it can be speculated that anti-sclerostin antibody treatment, which is a promising option for severe osteoporosis and surgical implant fixation, might have a role in T2DM treatment (36).…”
Section: Discussionmentioning
confidence: 64%
“…In patients with T2DM, the increase of serum sclerostin is associated with a significant decrease in the b-catenin serum concentration, suggesting, indeed, that sclerostin signaling is modulated in diabetes (31). On one hand, this gives support to the hypothesis that bone, which produces almost all the available sclerostin, may play a role also in glucose metabolism and insulin resistance (8,32,35). On the other hand, it can be speculated that anti-sclerostin antibody treatment, which is a promising option for severe osteoporosis and surgical implant fixation, might have a role in T2DM treatment (36).…”
Section: Discussionmentioning
confidence: 64%
“…Of the five studies reporting on bsALP, one reported a significant increase with TZDs [12] and no effect was seen in four [13,17,25,28]. Of the 11 studies reporting on PINP, three reported significant increases with TZDs [12,18,33], two showed significant decreases [27,31] and six found no effect [13-15, 17, 25, 28]. Of the six studies that reported on osteocalcin, one demonstrated a significant decrease with TZDs [14] and five showed no effect [21,23,25,28,31].…”
Section: Study Characteristicsmentioning
confidence: 95%
“…Figure 3 shows that there were no statistically significant differences in percentage change in BMD between the TZD group and controls following treatment withdrawal. 10 studies reporting on CTX, five reported significant increases with TZDs [12,17,18,28,33] and five showed no effect [13-15, 25, 31]. Of the five studies reporting on bsALP, one reported a significant increase with TZDs [12] and no effect was seen in four [13,17,25,28].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Other mechanisms, beside the alteration of adipocyte and osteoblast differentiation, could be involved in the detrimental action of thiazolidinediones on bone metabolism. An increase of markers of bone turnover has been reported with both pioglitazone and rosiglitazone, compared with either metformin or placebo in randomized trials (12,13), although some studies disagree (14). It is possible that the reduction in bone density is partly due to increased bone reabsorption, as suggested by the higher number of circulating osteoclast precursors in women treated with thiazolidinediones (15).…”
Section: Mini-reviewmentioning
confidence: 99%